2010
DOI: 10.1038/pj.2010.4
|View full text |Cite
|
Sign up to set email alerts
|

Significantly improved performance of rubber/silica composites by addition of sorbic acid

Abstract: Sorbic acid (SA) was used to improve the performance of styrene-butadiene rubber (SBR)/silica composites by direct blending. The mechanisms for the significantly improved performance were studied by X-ray photoelectron spectroscopy, X-ray diffraction and by the determinations of bound rubber content and crosslink density. The strong interfacial bonding between silica and the rubber matrix resulted from SA-intermediated linkages. Significantly improved dispersion of silica by virtue of the interactions between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…When the elastic sample (T4Tg) is loaded with dynamic strain, the rubber chains in the interfacial region may readily be deformed due to a weakened filler network and altered interfacial structures. 27,54 Aggravated interfacial chain motion then leads to higher loss at temperatures above the glass transition.…”
Section: Mechanical Performance Of the Sbr/silica Vulcanizatesmentioning
confidence: 99%
See 2 more Smart Citations
“…When the elastic sample (T4Tg) is loaded with dynamic strain, the rubber chains in the interfacial region may readily be deformed due to a weakened filler network and altered interfacial structures. 27,54 Aggravated interfacial chain motion then leads to higher loss at temperatures above the glass transition.…”
Section: Mechanical Performance Of the Sbr/silica Vulcanizatesmentioning
confidence: 99%
“…[45][46][47] Reactivity of MimS on SBR and the interaction between poly(MimS) and silica Many researchers, including us, have confirmed the polymerizability of sorbyl substances such as sorbic acid and sorbates. [25][26][27][48][49][50] Although the reactivity of sorbyl in MimS should be different from sorbic acid, it is believed that it can undergo polymerization via the free radical mechanism. The polymerization of MimS was characterized by FTIR spectroscopy (Figure 4).…”
Section: Effect Of Mims On Filler Networking In Uncured Rubber Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of the high cost of metal (meth)acrylates and the corrosive nature of (meth)acrylic acid, exploring alternative reactive metal carboxylates was still necessary. Recently, we demonstrated that sorbic acid (SA), a common food preservative, was very effective in promoting the interfacial properties of silica or halloysite reinforced rubber and it is revealed that zinc disorbate (ZDS) was in situ formed in those systems [19][20][21]. In the present work, we attempted to use the in situ formed ZDS as the sole reinforcing agent for nitrile rubber (NBR).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] In this context, we reported that the fine tuning of size and shape in silica nanoparticles (NPs), along with their surface organic functionalization, favors filler interaction with the polymer and allows the formation of a homogeneous and continuous percolative filler network which enhances the mechanical properties of the ensuing composites. 7,8 Recently, we also demonstrated that particles having an anisotropic shape are able to self-assemble in nanostructures inside the rubber matrix, providing an increase of the rubber immobilized at the filler/rubber interface and a consequent improvement of the mechanical properties.…”
Section: Introductionmentioning
confidence: 99%